The Relationship between the Weight of a Backpack and Lowback Pain in Children Ages 10 to 12 Years Old - Sinuraya, Elida; Harahap, Nurlelasari (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Every parent expected their child to grow and develop well. Most of the children using a bag for bringing their school necessities every day. It needs attention because if they are using a backpack more than 10 percent of their weight, it can have a negative impact on them. Heavy backpack causes the child to bend forward to support the weight on their back. it will change the curvature of the spine and will cause back pain. The purpose of this study is to determine the relationship between the weight of the backpack and low back pain in children ages 10 to 12 years old. A descriptive correlation study was applied to achieve the purpose of this study. The participants were 75 children from elementary school in Bahal Batu Barungun tengah in North Sumatra, Indonesia. Data was collected from Februari to June 2018. Digital scale was used measured the weight of the backpack and Low back pain was assessed using a validated questionnaire. The association of low back pain and backpack weight was analyzed using Chi-square test. The results showed that the majority of the weight of children ages 10 to 12 years old is heavy (68.0%) and low back pain in children ages 10 to 12 years old (80%). There is a relationship between the weight of a backpack and low back pain in children ages 10 to 12 years old (p <0.05). Suggestion for all parents to check the weight of a backpack their children bring to school